Determination of the physiological quality of corn seeds by infrared equipment - Cinthia Vieira Golfi Andriazzi; Debora Kelli Rocha; Ceci Castilho Custódio (Journal of Seed Science, 2023)
Abstract: The use of infrared equipment to evaluate the physiological quality of seeds has become an extremely important technique for the operation, since it is not destructive to the seed and is safe for the operator. The experiment was divided into two stages, in the first, the controlled deterioration curve was carried out, and in the second stage, the validation of the NIR XDS process was carried out, through modeling for classification of the lots. The technique used for controlled deterioration proved to be efficient to show that with a higher band ratio index, the spectrum has a greater amplitude and lower physiological potential, the opposite is also valid, when the band index is smaller, the spectrum amplitude is smaller and higher values of germination and vigor were observed. For the second stage, it was concluded that spectra generated by NIR XDS equipment can be used quickly for decision making on corn seed samples, considering a binary classification for the parameters of germination and vigor according to the approval and disapproval values of lots considered in this study.